Comparison of initial treatment with and without corticosteroids for suspected acute pancreatitis in dogs. (13th March 2019) - Okanishi, H.; Nagata, T.; Nakane, S.; Watari, T.
Abstract : Objectives: To compare initial treatment with and without corticosteroids for acute pancreatitis in dogs and investigate the therapeutic efficacy and prognosis. Materials and Methods: Sixty‐five dogs were included in this non‐blinded, non‐randomised clinical study. Dogs with acute pancreatitis received treatment either with dose of 1 mg/kg/day prednisolone (n=45) or without prednisolone (n=20). Response to treatment was based on changes in the C‐reactive protein concentration, improvement in clinical signs, duration of hospitalisation, mortality and recurrence rate. Results: From the third day of hospitalisation, C‐reactive protein concentration was significantly lower in the prednisolone group than that in the non‐prednisolone group. The number of days required to reach a C‐reactive protein concentration of <2 mg/dL and clinical score of ≤2 was significantly lower in the prednisolone group. The mortality rate 1 month after discharge was significantly lower in the prednisolone group (11.3% versus 46.1%). Clinical Significance: In dogs with acute pancreatitis, initial treatment with prednisolone resulted in earlier reductions in C‐reactive protein concentration and earlier improvement of clinical signs.